(untitled) (Journal of Universal Excellence, 2026)
Research question: How family influence lifelong learning of older people in retirement homes? Purpose: The future of family and family relations, which include also older persons will be characterised by decreasing impact of kinship and increasing influence of friendship. The purpose of the thesis is confirmation of family orientation to fulfil needs of individuals for love, activities, care, friendship, support and safety in the changes which take place in individual and family life of older people, as well as in their lifelong learning. Results: It is established, that one of the tasks of retirement home management is activation of family (relatives) with regard to engagement of older people in lifelong learning in the retirement home. Ageing should be a joint family project, what demands more useful knowledge in a field of family, and often also a professional help of social work experts. Organisation: Performed study will help retirement home management to encourage even more intense engagement of families (relatives) in lifelong learning activities of older people in institutional care. Society: The thesis and study will contribute to improvement of living conditions of older people in the society in general, in retirement homes, as well as noninstitutional care in a sphere of lifelong learning. Originality: It is the first study of this kind in a field of establishing meaning of lifelong learning of older people in retirement homes. Limitations/further research: The study was limited only to retirement homes in Pomurje region. Further research could examine the total population of older people in Slovenia and make a comparison to the meaning of lifelong learning of older people in other member states of the European Union.